Solutions of some partial differential equations with variable coefficients by properties of monogenic functions - Pogorui, A.A.; Rodriguez-Dagnino, R.M. (Український математичний вісник, 2016)
In this paper we study some partial differential equations by using properties of Gateaux differentiable functions on commutative algebra. It is proved that components of differentiable functions satisfy some partial differential equations with coefficients related with properties of bases of subspaces of the corresponding algebra.